GELSOLINE, ADIPSIN AND TAURINE LEVELS IN PLASMA AND URINE AS AN EARLY INDICATOR OF DIABETIC NEPHROPATHY IN CHILDREN WITH TYPE 1 DIABETES MELLITUS - Kayaduman, Arzu; Kara, Aslihan; Aydin, Suleyman; Esen, Ihsan (Springer, 2023)
[Abstract Not Available]